A water-based chromium-free zinc-aluminum coating and preparation method thereof

By designing a water-based chromium-free zinc-aluminum coating composed of multi-components, using zinc-aluminum powder and silane coupling agents to form raw materials, the coating sintering and curing temperature is reduced, and the problem of high curing temperature of existing coatings is solved, and the problem of existing coatings is achieved. Energy saving and coating density.

CN116769335BActive Publication Date: 2025-02-11SICHUAN TIANTENG TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310713560.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2025-02-11
Estimated Expiration
2043-06-16

AI Technical Summary

Technical Problem

The curing temperature of existing water-based chromium-free zinc-aluminum anticorrosion coatings is high, resulting in greater energy consumption.

Method used

By designing an aqueous chromium-free zinc-aluminum coating composed of the first component, the second component and the third component, zinc-aluminum powder, dispersant, silane coupling agent and other raw materials, zinc-aluminum superimposed layer by layer The powder forms complex oxides through the sintering process, which closely combines to form a dense and firm protective layer, reducing the sintering and curing temperature of the coating.

Benefits of technology

The coating sintering curing temperature is reduced to about 150°C, saving part of the curing energy consumption, and ensuring the density and corrosion resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116769335B_ABST
    Figure CN116769335B_ABST
Patent Text Reader

Abstract

The present invention provides a water-based chromium-free zinc-aluminum coating and a preparation method thereof. The water-based chromium-free zinc-aluminum coating consists of a first component, a second component and a third component. The raw materials of the first component include zinc-aluminum powder, a dispersant, deionized water, a high-boiling alcohol, an organosilicon defoamer and a silane coupling agent. The raw materials of the second component include deionized water, a low-boiling alcohol, a silane coupling agent and a thickener. The raw materials of the third component include deionized water, a low-boiling alcohol, triethylamine or a water-based amino resin and sodium dodecyl sulfate. The present invention is designed through the composition of the water-based chromium-free zinc-aluminum coating. The zinc-aluminum powders stacked on top of each other are tightly combined to form a dense and firm protective layer through the complex oxides generated during the sintering process, so that the coating can be well isolated from the corrosive medium. At the same time, due to the synergistic effect between the various raw materials, the coating sintering and curing temperature can be reduced to about 150°C at the lowest, saving some energy consumption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to a water-based chromium-free zinc-aluminum coating and a preparation method thereof. Background Art

[0002] Zinc-aluminum coating (Dacromet coating) has been widely used in the fields of automobile, medicine, electricity, petroleum and military industry because of its advantages that cannot be matched by traditional electroplating and hot-dip galvanizing, such as no hydrogen embrittlement, less pollution and good corrosion resistance. However, the use of Dacromet coating has been subject to increasingly strict restrictions because it contains highly toxic and highly carcinogenic substances such as chromic anhydride. Therefore, the development of a new environmentally friendly treatment technology that does not contain hexavalent chromium to replace Dacromet has become a research hotspot in the field of metal surface corrosion protection.

[0003] For example, a Chinese invention patent (publication number: CN111073507B, announcement date: 20220325) discloses a water-based chrome-free zinc-aluminum anti-corrosion coating and a preparation method thereof. The water-based chrome-free zinc-aluminum anti-corrosion coating is composed of a first component and a second component, the mass ratio of the first component to the second component is 1 to 1.5, the first component includes the following components, zinc-aluminum powder, dispersant, wetting agent, vinyl silane coupling agent alcohol solution, defoamer, adhesion promoter, leveling agent, lamellar filler; the second component includes the following components, silane coupling agent C, methanol and deionized water.

[0004] However, the curing temperature of the water-based chromium-free zinc-aluminum anti-corrosion coating exceeds 250°C, the coating curing temperature is relatively high, and the energy consumption is relatively large. Summary of the invention

[0005] The present invention aims to solve the problem of high curing temperature of existing water-based chromium-free zinc-aluminum anticorrosive coatings, and provides a chromium-free zinc-aluminum coating and a preparation method thereof. The coating sintering curing temperature can be reduced to about 150° C. at the lowest, thereby saving some curing energy consumption.

[0006] The technical solution adopted by the present invention is:

[0007] A water-based chromium-free zinc-aluminum coating, consisting of a first component, a second component and a third component, wherein the weight ratio of the first component, the second component and the third component is 1-1.5:1:0.1-0.5;

[0008] In parts by mass, the constituent materials of the first component include:

[0009] Zinc aluminum powder, 20~50 parts,

[0010] Dispersant, 1~5 parts,

[0011] Deionized water, 10~30 parts,

[0012] High boiling point alcohol, 20~50 parts,

[0013] Silicone defoamer, 0.1~0.5 parts,

[0014] Silane coupling agent, 1~3 parts;

[0015] In parts by mass, the constituent materials of the second component include:

[0016] Deionized water, 10~15 parts,

[0017] Low boiling point alcohol, 10-15 parts,

[0018] Silane coupling agent, 10~15 parts,

[0019] Thickener, 0.05~0.1 parts,

[0020] In parts by mass, the constituent materials of the third component include:

[0021] Deionized water, 10~25 parts,

[0022] Low boiling point alcohol, 10~25 parts,

[0023] Triethylamine or water-based amino resin, 10-25 parts,

[0024] Sodium lauryl sulfate, 0.1~0.5 parts.

[0025] Furthermore, the zinc-aluminum powder consists of flaky aluminum powder, spherical aluminum powder, flaky zinc powder and spherical zinc powder, and the weight ratio of the flaky aluminum powder, the spherical aluminum powder, the flaky zinc powder and the spherical zinc powder is 1:0.1~0.5:4~10:0.4~1.

[0026] Furthermore, the flake aluminum powder has a diameter of 10 to 25 μm and a thickness of 0.1 to 0.5 μm;

[0027] And / or, the particle size of the spherical aluminum powder is 1-2 μm;

[0028] And / or, the flaky zinc powder has a diameter of 5 to 20 μm and a thickness of 0.1 to 0.5 μm;

[0029] And / or, the particle size of the spherical zinc powder is 1-2 μm.

[0030] Furthermore, when the flaky aluminum powder, the spherical aluminum powder, the flaky zinc powder and the spherical zinc powder are mixed, they are ground and mixed together with polyethylene glycol PEG-400 in an inert atmosphere for 20 to 30 minutes; wherein the amount of polyethylene glycol PEG-400 used is 0.3 to 0.5% of the total weight of the zinc and aluminum powder.

[0031] Furthermore, the dispersant is OP-10 or NP-9.

[0032] Further, the high boiling point alcohol is ethylene glycol or propylene glycol;

[0033] And / or, the low boiling point alcohol is methanol or ethanol.

[0034] Furthermore, the silane coupling agent is one or more of an aminosilane coupling agent, an epoxysilane coupling agent, and other functional silanes.

[0035] Further, the aminosilane coupling agent is one or more of aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrialkoxysilane, 3-phenylaminopropyltrialkoxysilane, aminopropylmethyldialkoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldialkoxysilane, N-n-butyl-3-aminopropyltrialkoxysilane, and 3-(diethylenetriamine)propyltrialkoxysilane;

[0036] And / or, the epoxysilane coupling agent is one or more of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropylmethyldimethoxysilane, and 3-glycidyloxypropylmethyldiethoxysilane;

[0037] And / or, the other functional silane is one or more of ethyl orthosilicate, propyltrimethoxysilane, phenyltrimethoxy, γ-methacryloxypropyltrimethoxysilane, tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, methylphenyldimethoxysilane, vinyltrimethoxysilane, 3-(methacryloxy)propyltrimethoxysilane, and 3-(methacryloxy)propylmethyldimethoxysilane.

[0038] Furthermore, the thickener is one or more of hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose and polypropylene glycol.

[0039] The method for preparing the aforementioned water-based chromium-free zinc-aluminum coating comprises the following steps:

[0040] Step S1, weighing the constituent raw materials of the first component according to the ratio, first stirring and mixing the dispersant, deionized water and high-boiling alcohol, stirring for a period of time, adding half of the zinc-aluminum powder and the silane coupling agent and continuing to stir, stirring for a period of time, continuing to add the remaining zinc-aluminum powder and the silane coupling agent and continuing to stir, and finally adding the organosilicon defoamer, continuing to stir for a period of time, to obtain a first slurry;

[0041] Step S2, weighing the raw materials of the second component according to the ratio, first stirring and mixing the deionized water and the low-boiling alcohol, stirring for a period of time, adding the silane coupling agent and continuing to stir, and finally adding the thickener and continuing to stir for a period of time to obtain the second slurry;

[0042] Step S3, weighing the raw materials of the third component according to the ratio, stirring and mixing deionized water, low boiling point alcohol and sodium dodecyl sulfate, stirring for a period of time, adding triethylamine or aqueous amino resin, and continuing to stir for a period of time to obtain a third slurry;

[0043] Step S4, weigh the first slurry, the second slurry and the third slurry according to the ratio, first mix the second slurry and part of the third slurry, stir for a period of time, add the first slurry and continue stirring, finally add the remaining third slurry, continue stirring for a period of time, and obtain a water-based chromium-free zinc-aluminum coating.

[0044] The beneficial effects of the present invention are:

[0045] 1. The present invention provides a water-based chromium-free zinc-aluminum coating, which consists of a first component, a second component and a third component. The raw materials of the first component include: zinc-aluminum powder, 20 to 50 parts, dispersant, 1 to 5 parts, deionized water, 10 to 30 parts, high boiling point alcohol, 20 to 50 parts, silicone defoamer, 0.1 to 0.5 parts, silane coupling agent, 1 to 5 parts. The raw materials of the second component include: deionized water, 10 to 15 parts, low boiling point alcohol, 10 to 15 parts, silane coupling agent, 10 to 15 parts, thickener, 0.05 to 0.1 parts. The raw materials of the third component include: deionized water, 10 to 25 parts, low boiling point alcohol, 10 to 25 parts, triethylamine or water-based amino resin, 10 to 25 parts, sodium dodecyl sulfate, 0.1 to 0.5 parts. The present invention is designed through the composition of water-based chromium-free zinc-aluminum coating. The superimposed zinc and aluminum powders are tightly combined through the complex oxides generated in the sintering process to form a dense and firm protective layer, which can effectively isolate the corrosive medium. At the same time, due to the synergistic effect between the various component raw materials, the sintering and curing temperature of the coating can be reduced to about 150°C at the lowest, saving some energy consumption.

[0046] 2. The present invention also provides a method for preparing a water-based chromium-free zinc-aluminum coating, which is simple to operate and has guaranteed quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0048] Figure 1 The process flow chart of the method for water-based chromium-free zinc-aluminum coating in the embodiment. DETAILED DESCRIPTION

[0049] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0050] The disclosure below provides many different embodiments or examples to realize different structures of the present invention. In order to simplify the disclosure of the present invention, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention.

[0051] The embodiments of the invention are described in detail below with reference to the accompanying drawings.

[0052] A method for water-based chromium-free zinc-aluminum coating, the process of which is as shown in the attached Figure 1 The method comprises the following steps:

[0053] Step S1, weighing the constituent raw materials of the first component according to the ratio, first stirring and mixing the dispersant, deionized water and high-boiling alcohol, stirring for a period of time (for example, 10 minutes), adding half of the zinc-aluminum powder and the silane coupling agent and continuing to stir, stirring for a period of time (for example, 20 minutes), continuing to add the remaining zinc-aluminum powder and the silane coupling agent and continuing to stir, and finally adding the organosilicon defoamer, continuing to stir for a period of time (for example, 10 minutes), to obtain a first slurry;

[0054] Step S2, weighing the raw materials of the second component according to the ratio, first stirring and mixing the deionized water and the low-boiling alcohol, stirring for a period of time (e.g., 10 minutes), adding the silane coupling agent and continuing to stir, and finally adding the thickener, and continuing to stir for a period of time (e.g., 10 minutes) to obtain the second slurry;

[0055] Step S3, weighing the constituent materials of the third component according to the ratio, stirring and mixing deionized water, low boiling point alcohol and sodium dodecyl sulfate (for example, for 10 minutes), adding triethylamine or aqueous amino resin after stirring for a period of time, and continuing to stir for a period of time (for example, for 10 minutes) to obtain a third slurry;

[0056] Step S4, weigh the first slurry, the second slurry and the third slurry according to the ratio, first mix the second slurry and part of the third slurry, stir for a period of time (for example, 10 minutes), add the first slurry and continue stirring, and finally add the remaining third slurry, continue stirring for a period of time (for example, 30 minutes) to obtain a water-based chromium-free zinc-aluminum coating.

[0057] The zinc-aluminum powder is composed of flaky aluminum powder, spherical aluminum powder, flaky zinc powder and spherical zinc powder, and the weight ratio of the flaky aluminum powder, the spherical aluminum powder, the flaky zinc powder and the spherical zinc powder is 1:0.1~0.5:4~10:0.4~1.

[0058] The flake diameter of the aluminum powder is 10-25 μm, and the thickness is 0.1-0.5 μm; the particle size of the spherical aluminum powder is 1-2 μm; the flake diameter of the zinc powder is 5-20 μm, and the thickness is 0.1-0.5 μm; the particle size of the spherical zinc powder is 1-2 μm.

[0059] When the flaky aluminum powder, the spherical aluminum powder, the flaky zinc powder and the spherical zinc powder are mixed, they are ground and mixed together with polyethylene glycol PEG-400 in an inert atmosphere for 20 to 30 minutes; wherein the amount of polyethylene glycol PEG-400 used is 0.3 to 0.5% of the total weight of the zinc and aluminum powder. Through the grinding action, the polyethylene glycol PEG-400 is coated on the surface of the flaky aluminum powder, the spherical aluminum powder, the flaky zinc powder and the spherical zinc powder, which plays a certain isolation role and can also improve their dispersion performance.

[0060] The dispersant is OP-10 or NP-9.

[0061] The high boiling point alcohol is ethylene glycol or propylene glycol; the low boiling point alcohol is methanol or ethanol.

[0062] The silane coupling agent is one or more of an aminosilane coupling agent, an epoxysilane coupling agent, and other functional silanes.

[0063] The aminosilane coupling agent is one or more of aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrialkoxysilane, 3-phenylaminopropyltrialkoxysilane, aminopropylmethyldialkoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldialkoxysilane, N-n-butyl-3-aminopropyltrialkoxysilane, and 3-(diethylenetriamino)propyltrialkoxysilane.

[0064] The epoxysilane coupling agent is one or more of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropylmethyldimethoxysilane, and 3-glycidyloxypropylmethyldiethoxysilane.

[0065] The other functional silanes are one or more of ethyl orthosilicate, propyltrimethoxysilane, phenyltrimethoxy, γ-methacryloxypropyltrimethoxysilane, tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, methylphenyldimethoxysilane, vinyltrimethoxysilane, 3-(methacryloxy)propyltrimethoxysilane, and 3-(methacryloxy)propylmethyldimethoxysilane.

[0066] The thickener is one or more of hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose and polypropylene glycol.

[0067] The following is a more specific example for illustration. The water-based chromium-free zinc-aluminum coatings of Examples 1 to 28 were prepared according to the above method, and the specific compositions are shown in Tables 1 and 2.

[0068] Table 1 Raw material composition of water-based chromium-free zinc-aluminum coatings of Examples 1 to 12

[0069]

[0070] Table 1-1 Raw material composition of water-based chromium-free zinc-aluminum coatings of Examples 1 to 12

[0071]

[0072] Table 1-2 Raw material composition of water-based chromium-free zinc-aluminum coatings of Examples 1 to 12

[0073]

[0074] Among them, in Examples 1 to 12, the zinc-aluminum powder consists of flaky aluminum powder, spherical aluminum powder, flaky zinc powder and spherical zinc powder, and the weight ratio of the flaky aluminum powder, the spherical aluminum powder, the flaky zinc powder and the spherical zinc powder is 1:0.25:8:0.4.

[0075] Table 2 Raw material composition of water-based chromium-free zinc-aluminum coatings of Examples 13 to 28

[0076]

[0077] Table 2-1 Raw material composition of water-based chromium-free zinc-aluminum coatings of Examples 13 to 28

[0078]

[0079] Table 2-2 Raw material composition of water-based chromium-free zinc-aluminum coatings of Examples 13 to 28

[0080]

[0081] Table 2-3 Raw material composition of water-based chromium-free zinc-aluminum coatings of Examples 13 to 28

[0082]

[0083] The difference is that in Examples 13 to 24, the zinc-aluminum powder consists of flaky aluminum powder, spherical aluminum powder, flaky zinc powder and spherical zinc powder, and the weight ratio of the flaky aluminum powder, the spherical aluminum powder, the flaky zinc powder and the spherical zinc powder is 1:0.25:8:0.4.

[0084] In Example 25, the zinc-aluminum powder consists of flaky aluminum powder, spherical aluminum powder, flaky zinc powder and spherical zinc powder, and the weight ratio of the flaky aluminum powder, the spherical aluminum powder, the flaky zinc powder and the spherical zinc powder is 1:0.1:4:0.4.

[0085] In Example 26, the zinc-aluminum powder consists of flaky aluminum powder, spherical aluminum powder, flaky zinc powder and spherical zinc powder, and the weight ratio of the flaky aluminum powder, the spherical aluminum powder, the flaky zinc powder and the spherical zinc powder is 1:0.5:4:0.4.

[0086] In Example 27, the zinc-aluminum powder consists of flaky aluminum powder, spherical aluminum powder, flaky zinc powder and spherical zinc powder, and the weight ratio of the flaky aluminum powder, the spherical aluminum powder, the flaky zinc powder and the spherical zinc powder is 1:0.1:10:1.

[0087] In Example 28, the zinc-aluminum powder consists of flaky aluminum powder, spherical aluminum powder, flaky zinc powder and spherical zinc powder, and the weight ratio of the flaky aluminum powder, the spherical aluminum powder, the flaky zinc powder and the spherical zinc powder is 1:0.5:10:1.

[0088] The water-based chromium-free zinc-aluminum coatings of Comparative Examples 1 to 5 were prepared according to the aforementioned method, and the specific compositions are shown in Table 3.

[0089] Table 3 Raw material composition of water-based chromium-free zinc-aluminum coatings of comparative examples 1 to 5

[0090]

[0091] The difference is that in comparative example 1, the zinc-aluminum powder is composed of flaky aluminum powder, spherical aluminum powder, flaky zinc powder and spherical zinc powder, and the weight ratio of the flaky aluminum powder, the spherical aluminum powder, the flaky zinc powder and the spherical zinc powder is 1:0.25:8:0.4. When the water-based chromium-free zinc-aluminum coating is prepared, the first slurry, the second slurry and the third slurry are not separated, and all the raw materials of the coating are added at one time for mixing.

[0092] In comparative example 2, the zinc-aluminum powder is composed of flaky aluminum powder, spherical aluminum powder, flaky zinc powder and spherical zinc powder, and the weight ratio of the flaky aluminum powder, the spherical aluminum powder, the flaky zinc powder and the spherical zinc powder is 1:0.25:8:0.4. No silane coupling agent is added to the first component of the water-based chromium-free zinc-aluminum coating.

[0093] In comparative example 3, the zinc-aluminum powder is composed of flaky aluminum powder, spherical aluminum powder, flaky zinc powder and spherical zinc powder, and the weight ratio of the flaky aluminum powder, the spherical aluminum powder, the flaky zinc powder and the spherical zinc powder is 1:0.25:8:0.4. The water-based chromium-free zinc-aluminum paint has no third component.

[0094] In Control Example 4, the zinc-aluminum powder consists of flaky aluminum powder and flaky zinc powder, and the weight ratio of the flaky aluminum powder to the flaky zinc powder is 1:8.

[0095] In comparative example 5, the zinc-aluminum powder is composed of flaky aluminum powder, spherical aluminum powder, flaky zinc powder and spherical zinc powder, and the weight ratio of the flaky aluminum powder, the spherical aluminum powder, the flaky zinc powder and the spherical zinc powder is 1:0.25:8:0.4. Sodium lauryl sulfate is not added to the third component of the water-based chromium-free zinc-aluminum paint.

[0096] The water-based chromium-free zinc-aluminum coatings prepared in Examples 1 to 28 and Comparative Examples 1 to 5 were sprayed onto the steel sheets after degreasing pretreatment, and the coatings were coated and baked twice: 150 to 260° C., 30 to 60 min, and then the coating thickness, adhesion and neutral salt spray tests were performed. The coating test results are shown in Tables 3 and 4.

[0097] Table 3 Coating test results of Examples 1 to 28

[0098]

[0099] Table 3-1 Coating test results of Examples 1 to 28

[0100]

[0101] Table 3-2 Coating test results of Examples 1 to 28

[0102]

[0103] Table 3-3 Coating test results of Examples 1 to 28

[0104]

[0105] Table 3-4 Coating test results of Examples 1 to 28

[0106]

[0107] Table 4 Coating test results of control examples 1 to 5

[0108]

[0109] From the data in Table 3, it can be seen that the water-based chromium-free zinc-aluminum coating prepared by the method in this embodiment has low-temperature curing performance, and the lowest curing temperature can be 150° C., which can save some energy consumption.

[0110] At the same time, combined with the data in Table 3 and Table 4, it can be seen that, on the one hand, compared with mixing all the constituent raw materials at one time, the method of configuring the first component, the second component and the third component into the first slurry, the second slurry and the third slurry respectively, and then mixing them is beneficial to improving the dispersibility of the raw materials and improving the curing and film-forming properties of the coating.

[0111] On the other hand, adding silane coupling agent into the first component and adhering to the surface of flaky aluminum powder, spherical aluminum powder, flaky zinc powder and spherical zinc powder is beneficial to improve the dispersibility of flaky aluminum powder, spherical aluminum powder, flaky zinc powder and spherical zinc powder, and at the same time improves the contact and mixing effect of flaky aluminum powder, spherical aluminum powder, flaky zinc powder and spherical zinc powder with the coupling agent in the second component, and can play a certain role in reducing the curing temperature, improving the performance of the coating film layer, and finally curing to obtain a dense film layer.

[0112] On the other hand, by adding the third component in the present invention, the low-temperature curing performance of the coating can be improved, and the coating can be accelerated to cure and form a film at a relatively low temperature.

[0113] On the other hand, compared with the combination of flaky aluminum powder and flaky zinc powder, the combination of flaky aluminum powder, spherical aluminum powder, flaky zinc powder and spherical zinc powder used in the present invention is equivalent to improving the grading of metal powders, which is beneficial to improving the density of the film layer.

[0114] Finally, the present invention introduces sodium dodecyl sulfate into the third component to improve the dispersibility of the third component, accelerate its contact and mixing with the first component and the second component, and realize low-temperature curing of the coating film.

Claims

1. A water-based chromium-free zinc-aluminum coating, characterized in that: It consists of a first component, a second component and a third component, wherein the weight ratio of the first component, the second component and the third component is 1-1.5:1:0.1-0.5; In parts by mass, the constituent materials of the first component include: Zinc aluminum powder, 20~50 parts, Dispersant, 1~5 parts, Deionized water, 10~30 parts, High boiling point alcohol, 20~50 parts, Silicone defoamer, 0.1~0.5 parts, Silane coupling agent, 1~3 parts; In parts by mass, the constituent materials of the second component include: Deionized water, 10~15 parts, Low boiling point alcohol, 10-15 parts, Silane coupling agent, 10~15 parts, Thickener, 0.05~0.1 parts, In parts by mass, the constituent materials of the third component include: Deionized water, 10~25 parts, Low boiling point alcohol, 10~25 parts, Triethylamine or water-based amino resin, 10-25 parts, Sodium lauryl sulfate, 0.1-0.5 parts; Wherein, the silane coupling agent is one or more of an aminosilane coupling agent, an epoxysilane coupling agent, and other functional silanes; The aminosilane coupling agent is aminopropyltriethoxysilane; The epoxysilane coupling agent is one or more of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, and 3-glycidyloxypropylmethyldiethoxysilane; The other functional silane is one or more of ethyl orthosilicate, propyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, tetramethoxysilane, methyl trimethoxysilane, phenyl trimethoxysilane, diphenyl dimethoxysilane, methyl phenyl dimethoxysilane, vinyl trimethoxysilane, and 3-(methacryloxy)propyl methyl dimethoxysilane; The zinc-aluminum powder is composed of flaky aluminum powder, spherical aluminum powder, flaky zinc powder and spherical zinc powder, and the weight ratio of the flaky aluminum powder, the spherical aluminum powder, the flaky zinc powder and the spherical zinc powder is 1:0.1~0.5:4~10:0.4~1; The preparation method of water-based chromium-free zinc-aluminum coating comprises the following steps: Step S1, weighing the constituent raw materials of the first component according to the ratio, first stirring and mixing the dispersant, deionized water and high-boiling alcohol, stirring for a period of time, adding half of the zinc-aluminum powder and the silane coupling agent and continuing to stir, stirring for a period of time, continuing to add the remaining zinc-aluminum powder and the silane coupling agent and continuing to stir, and finally adding the organosilicon defoamer, continuing to stir for a period of time, to obtain a first slurry; Step S2, weighing the raw materials of the second component according to the ratio, first stirring and mixing the deionized water and the low-boiling alcohol, stirring for a period of time, adding the silane coupling agent and continuing to stir, and finally adding the thickener and continuing to stir for a period of time to obtain the second slurry; Step S3, weighing the raw materials of the third component according to the ratio, stirring and mixing deionized water, low boiling point alcohol and sodium dodecyl sulfate, stirring for a period of time, adding triethylamine or aqueous amino resin, and continuing to stir for a period of time to obtain a third slurry; Step S4, weigh the first slurry, the second slurry and the third slurry according to the ratio, first mix the second slurry and part of the third slurry, stir for a period of time, add the first slurry and continue stirring, finally add the remaining third slurry, continue stirring for a period of time, and obtain a water-based chromium-free zinc-aluminum coating.

2. The water-based chromium-free zinc-aluminum coating according to claim 1, characterized in that: The flake aluminum powder has a diameter of 10 to 25 μm and a thickness of 0.1 to 0.5 μm; The particle size of the spherical aluminum powder is 1-2 μm; The flaky zinc powder has a diameter of 5 to 20 μm and a thickness of 0.1 to 0.5 μm; The particle size of the spherical zinc powder is 1-2 μm.

3. The water-based chromium-free zinc-aluminum coating according to claim 1, characterized in that: When the flaky aluminum powder, the spherical aluminum powder, the flaky zinc powder and the spherical zinc powder are mixed, they are ground and mixed together with polyethylene glycol PEG-400 in an inert atmosphere for 20 to 30 minutes; wherein the amount of polyethylene glycol PEG-400 used is 0.3 to 0.5% of the total weight of the zinc and aluminum powder.

4. The water-based chromium-free zinc-aluminum coating according to claim 1, characterized in that: The dispersant is OP-10 or NP-9.

5. The water-based chromium-free zinc-aluminum coating according to claim 1, characterized in that: The high boiling point alcohol is ethylene glycol or propylene glycol; The low boiling point alcohol is methanol or ethanol.

6. The water-based chromium-free zinc-aluminum coating according to any one of claims 1 to 5, characterized in that: The thickener is one or more of hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose and polypropylene glycol.

Citation Information

Patent Citations

  • A water-based chromium-free zinc-aluminum anti-corrosion coating and its preparation method

    CN111073507B

  • Chromium-free zinc aluminum coating with low sintering temperature, as well as preparation method and application thereof

    CN106893485A

  • Coating mixture for base material immersed in seawater and preparation method of coating mixture

    CN112538305A

  • Preparation method of low-temperature curing environment-friendly water-based chromium-zinc-aluminum-free coating

    CN114410221A